Patient Preparation for 18 F FDG PET-CT scan A Short Communication - Begum, Fatima; Hussain, Raihan; Begum, Shamim Momtaz Ferdousi; Hasan, Mizanul (Bangladesh Journal of Nuclear Medicine, 2018)
Abstract not available Bangladesh J. Nuclear Med. 19(1): 68-69, January 2016